Mechanical and antibacterial properties of paper coated with chitosan - Sarani Zakaria,; Chin, Hua Chia; Wan Haslinda Wan Ahmad,; Hatika Kaco,; Soon, Wei Chook; Chi, Hoong Chan (Universiti Kebangsaan Malaysia, 2015)
Recent developments have found the viability of chitosan as a new alternative additive in the pulp and paper technology. This study was carried out to investigate the effect of chitosan as a paper coating which were prepared by dissolution in acetic acid solution. The mechanical properties of coated paper were improved significantly compared with non-coated paper. The FT-IR spectra showed peak evolution at 1558 cm-1 for coated paper due to the existence of amine group. Since FT-IR spectra for the coated paper was almost identical to the chitosan spectrum, it is assumed that there is an obvious physical interaction rather than the chemical interaction. The SEM micrographs showed that some of the chitosan has occupied the pores and some of them adhered only on the surface. This may be due to the chemical similarities between cellulose and chitosan which enhanced the strength of fiber matrixes via hydrogen bonding. The antibacterial property of coated paper showed that chitosan in dried form has no significant effect but effective when applied as wet solution.